Effect of Phosphate Concentration on Anodizing Process Efficiency and Aluminium Surface Hardness in 16% Sulfuric Acid Solution - Robby Sudarman; Retno Indarti; Nurcahyo Nurcahyo; Ahmad Fauzan; Agustinus Ngatin; Rony Pasonang Sihombing (Fluida, 2024)
One of the problems the aircraft industry faces is equipment that has decreased performance in the period before planning. The solution to this condition is that a material that has hard properties and is corrosion-resistant is needed. Aluminium is a metal that is applied as equipment in the industry because it has the characteristics of being light, strong, corrosion resistant and easy to shape, but has properties that are easy to deform, have low hardness and wear resistance. Anodizing process has the characteristics to improve the surface properties of aluminium metal in physical and mechanical properties. The anodizing process of aluminium metal using sulfuric acid solution produces a thicker oxide layer than in other solutions, such as phosphoric acid solution. This research studied the effect of phosphoric acid concentration on process efficiency, oxide layer thickness, and the hardness of the anodized oxide layer in 16% sulfuric acid solution. Phosphoric acid solution concentration varied from 0; 0.5; 1;2;4; and 8% in 16% sulfuric acid solution at 5 Volts voltage or 1.12 A/dm2 current density with 25 minutes processing time. The results showed that the anodizing process in 16% sulfuric acid solution had the lowest efficiency of 19.3% after adding variations in the concentration of phosphoric acid. These conditions reached the optimum in 16% sulfuric acid solution with the addition of 1% phosphoric acid; 26.6 mg oxide mass; 50.33% efficiency; 90.48 mg/dm2 oxide layer thickness and 86.57 HV metal surface hardness